Altered expression of KCC2 in GABAergic interneuron contributes prenatal stress-induced epileptic spasms in infant rat. (July 2016) - Baek, Hyunjung; Yi, Min-Hee; Pandit, Sudip; Park, Jin Bong; Kwon, Hyeok Hee; Zhang, Enji; Kim, Sena; Shin, Nara; Kim, Eunjee; Lee, Young Ho; Kim, Yonghyun; Kim, Dong Woon; et al.
Abstract: Long-term stress during pregnancy causes neurologic deficits to offspring with altered gamma-aminobutyric acid (GABA) system in the brain. However, it is not clear how prenatal stress affects the maturing GABAergic interneurons and the resulting abnormalities in infantile seizures. Here, we showed that prenatal stress alters the maturation of GABA inhibitory system using a seizure model induced by prenatal stress. Prenatal stress with betamethasone or acute immobilization stress (AIS) on gestational day 15 increased the seizure susceptibility to N -methyl-d -aspartate-triggered spasms on postnatal day 15. The expression of GABA was lower in the prenatally stressed group, which compromise the decrease of glutamate decarboxylase 67-immunopositive cells. Prenatal stress markedly decreased the expression of K + /Cl − co-transporter (KCC2) in the cortex. GABA induced membrane depolarization demonstrated prenatal stress models had significant higher membrane depolarization compared to control. GABA increased KCC2 expression in cultured cortex-containing slices. Taken together, our results showed that prenatal stress with betamethasone or AIS altered the maturation of GABAergic progenitors and resulted in the lack of GABA input, which in turn, decreased KCC2 expression and lowered seizure threshold. We conclude that delayed GABA excitatory/inhibitory shift would render the cortical neuronal circuit more susceptible to excitatory input in prenatal stress induced seizure. Highlights: The expression of GABA and GAD67 were lower in the prenatally stressed group. Prenatal stress markedly decreased the expression of KCC2. Prenatal stress models had significant higher membrane depolarization compared to control. GABA increased KCC2 expression in cultured parietal cortex-containing slices.